'Artistic Exile' and Professional Failure: Brazilian Artists in New York in the 1960s and 1970s. Issue 4 (4th July 2021) - Jaremtchuk, Dária Gorete
Abstract: During the 1960s and 1970s, several Brazilian artists lived abroad in 'artistic exile'. This self-imposed displacement was precipitated by many things: the immaturity of the Brazilian art system, the lack of a market for young talents, institutions' failure to incorporate young artists' work, the United States' 'policies of attraction' and – of course – the military dictatorship in Brazil. What I propose here is an understanding of this displacement as a collective phenomenon, with historical and political dimensions and common motivations, in which artists experienced professional failure and were forced to redefine their creative processes. This article examines the trajectory of Amilcar de Castro and the works he produced during his 'artistic exile', as a way of comprehending aspects relevant to the displacement of this particular social group.